Studies of silver (AG) plasmonics structures integrated in side polished optical fiber sensor / Siti Fatimah Az Zahra Yusoff - Siti Fatimah Az Zahra , Yusoff (2018)
Many researchers have a great interest in nanotechnology field specifically in integrating plasmonics nanoparticles (NPs) as a device due to the unique characteristics owned by this noble metallic structure. Surface plasmon resonance (SPR) is the behavior of plasmonics which involves the study on the excitation of surface plasmon polaritons (SPP) at the metal-dielectric interface when interacting with light. In this work, the studies were focused on four main objectives, which are first; to study the effects of silver (Ag) structures with arbitrary shapes at random position, and secondly, is to study the effects of silver nanoparticles (AgNPs) with varying thickness of Ag films. Third objective is to design and fabricate side-polished optical fiber with the performance of AgNPs and lastly to study the application of Ag and the effects of TiO2 coated on the active area of the optical fiber as a humidity sensor. To accomplish the first objective, an arbitrary shape of Ag structures has been constructed experimentally using electrochemical deposition technique and the optical properties of the structures have been observed using Computer Simulation Technology (CST) Microwave Studio software. The shapes of Ag formed are flower-like structures with distinct petals looks. From the simulation, it has been proven that Ag flower-like structures show an obvious increment in an electromagnetic field due to the hotspots. Effect on varying thickness of AgNPs thin films has been further investigated. The Ag films were fabricated using electron beam (e-beam) evaporation techniques with four different thicknesses. The optical properties of the AgNPs has been observed using CST Microwave Studio software. Another layer of metal oxides, namely titanium oxide (TiO2) is introduced as another layer, covering the metallic layer in order to study the effect of metal oxides towards the improvement in detection. An optical fiber sensor has been fabricated using side polish unclad single mode fiber (SMF), with Ag and TiO2 coating. The main parameters are involved is to improve the quality of the sensor from sensitivity and accuracy point of view. With a right value of metallic layer and the polishing depth of the fiber, the quality of the sensor can be manipulated and optimized for a better application. The sensor with 7 nm Ag and TiO2 coating shows a better response as the percentage of relative humidity (% RH) increase.